Analisis Digitalisasi Administrasi Dokumen Berbasis Soechi Enterprise Application (SEA) pada Divisi Keuangan PT Soechi Lines Tbk - Ni Made Krisma Dwi Yuliati (Indo Publishing, 2026)
This study aims to analyze the implementation, constraints, and mitigation efforts of the SEA portal-based document digitalization in the Finance Division of PT Soechi Lines Tbk. Using a descriptive qualitative case study method, data were gathered through interviews, observations, and documentation from four informants (Finance Supervisor, Budgeting Supervisor, Budgeting Staff, and IT Staff) validated by triangulation techniques. The results indicate that the SEA portal enhances online invoice verification efficiency, yet its execution remains hybrid and has not fully achieved a paperless office. The primary constraint stems from procedural information asymmetry as official SOP documents are only known by the Division Manager, forcing staff to learn self-taught via informal peer-to-peer training. This issue is further exacerbated by technical glitches like blank automatic voucher numbers post-settlement and server overload during peak hours, triggering work duplication (double entry and manual printing). Mitigation efforts involve routine technical troubleshooting by the IT team and the finance staff's initiative to manually track files in the sharing folder finance based on chronological month and year classifications.